A Common Pathway of Root Growth Control and Response to CLE Peptides Through Two Receptor Kinases in Arabidopsis. Issue 2 (1st February 2018) - Racolta, Adriana; Nodine, Michael D; Davies, Kelli; Lee, Cameron; Rowe, Scott; Velazco, Yulemi; Wellington, Rachel; Tax, Frans E
Abstract: Racolta et al . show two different impacts of CLE peptide treatment of Arabidopsis roots. In all genotypes tested, they find increased proliferative.... Cell–cell communication is essential for plants to integrate developmental programs with external cues that affect their growth. Recent advances in plant signaling have uncovered similar molecular mechanisms in shoot, root, and vascular meristem signaling that involve receptor-like kinases and small, secreted peptides. Here, we report that the receptor-like kinases TOAD2/RPK2 and RPK1 regulate root growth by controlling cell proliferation and affecting meristem size. Two types of developmental alterations were observed upon exogenous CLE peptide application. The first type was detected in all plants treated, and comprise increased proliferative activity of cells in the stem cell niche and a delay of progression in differentiation of daughter cells. The second type was changes specific to the genotypes that are sensitive to CLE-driven root meristem inhibition and include a large decrease in the occurrence of cell divisions in longitudinal files, correlating with shorter meristems and cessation of root growth. The root meristems of toad2/rpk2 mutant plants are insensitive to the inhibitory effect of CLE17 peptide treatment, consistent with TOAD2/RPK2 function as a receptor for CLE peptides. In addition, a strong reduction in the expression of RPK1 protein upon CLE treatment, dependent on TOAD2/RPK2, suggests that these two RLKs mediate CLE signaling in a common pathway to control root growth.